Nonlinear Dynamics of Laminar-Turbulent Transition in Generalized 3D Kolmogorov Problem for Incompressible Viscous Fluid at Symmetric Solution Subset - Evstigneev, Nikolai M.; Magnitskii, Nikolai A. (Journal of Applied Nonlinear Dynamics, 2026)
A three dimensional Kolmogorov problem with extended forcing term for Navier-Stokes equations is considered. The Galerkin-Fourier method is applied and the symmetry preserving subset of solutions is considered. The bifurcation patterns are revealed through the numerical analysis of eigenvalues of the linearized perturbed system from the analytical main stationary solution and through the analysis of phase space trajectories that the system generates. It was found that the initial stage of laminar-turbulent transition undergoes pitchfork bifurcation, through which the system can either go through the series of cycle cascades or through continuous tori bifurcations in accordance with the FShM scenario.